2010
DOI: 10.1017/s1074070800003278
|View full text |Cite
|
Sign up to set email alerts
|

LL601 Contamination and Its Impact on U.S. Rice Prices

Abstract: LL601 is a genetically modified rice variety and unapproved for commercial use. Its presence was found in commercial shipments of U.S. rice in 2006. This article explores its impact on prices and volume marketed for both the United States and Thailand, the major export competitor. The results show a significantly adverse but short duration effect on the U.S. rice market and little to no effect on the Thai rice market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
18
1
Order By: Relevance
“…Detailed empirical research has found that product recalls can have a significant negative impact on firms across a range of performance measures, including operational performance (Hendricks & Singhal, 2005), share price Salin & Hooker, 2001;Wang et al, 2002), customer sales (Thomsen et al, 2006), consumer demand (Marsh et al, 2004), market movements (Palma et al, 2010), food prices (Li et al, 2010;, and prices on the futures market (Lusk & Schroeder, 2002). For example, Thomsen et al (2006) found that sales of recalled brands declined, on average, by 22% to 27% during the four to eight week time period after a recall announcement of Listeria.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed empirical research has found that product recalls can have a significant negative impact on firms across a range of performance measures, including operational performance (Hendricks & Singhal, 2005), share price Salin & Hooker, 2001;Wang et al, 2002), customer sales (Thomsen et al, 2006), consumer demand (Marsh et al, 2004), market movements (Palma et al, 2010), food prices (Li et al, 2010;, and prices on the futures market (Lusk & Schroeder, 2002). For example, Thomsen et al (2006) found that sales of recalled brands declined, on average, by 22% to 27% during the four to eight week time period after a recall announcement of Listeria.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has provided econometric methodologies to estimate adverse GE event-induced price effects that could be tied to declines in farm revenues and income for the nationwide crop sector subject to the contamination. Yet to date, some 34 years after Rubinfeld's (1985) previously mentioned comments, the literature does not provide a methodology to assess how such contamination events negatively influence prices and receipts at the farm-specific plaintiff level (Carter and Smith, 2007;Li et al, 2010).…”
Section: Purposementioning
confidence: 99%
“…Quite simply, when the United States has, on a number of occasions noted subsequently, announced that crop supplies have been contaminated with GM crop varieties or strains that have not been approved for human consumption, world demand for U.S. crops has fallen significantly and led to declines in U.S. farm prices, farm receipts, and farm income. There have been a number of studies that have estimated the U.S. national or "sectorlevel" crop price effects of such contamination events (see, e.g., Carter and Smith, 2007;Li et al, 2010). Yet to date, we have been unable to locate studies that provide a methodology to take such national or sector-level effects and translate them into adverse decreases in farm-specific prices received, cash receipts, and income for use by plaintiffs in litigation that usually follows contamination events.…”
Section: Introductionmentioning
confidence: 99%
“…But by that time, rice futures prices had fallen on the Chicago Board of Trade, and growers had entered into futures contracts at lower prices than anticipated (GAO 2008). University of Arkansas economists later confirmed a large and adverse (but shortlived) price drop (Li et al 2010).…”
Section: Libertylink Contaminationmentioning
confidence: 99%